Expression of the oncoprotein gankyrin and phosphorylated retinoblastoma protein in human testis and testicular germ cell tumor. (27th May 2014) - Ando, Satoshi; Matsuoka, Taeko; Kawai, Koji; Sugita, Shintaro; Joraku, Akira; Kojima, Takahiro; Suetomi, Takahiro; Miyazaki, Jun; Fujita, Jun; Nishiyama, Hiroyuki
<x xml:space="preserve">Abstract</x> Objective The oncoprotein, gankyrin, is known to facilitate cell proliferation through phosphorylation and degradation of retinoblastoma protein. In the present study, we evaluated the expression of gankyrin and phosphorylated retinoblastoma protein in human testis and testicular germ cell tumors. Methods The effects of suppression of gankyrin by locked nucleic acid on phosphorylation status of retinoblastoma and cell proliferation were analyzed using western blot analysis and testicular tumor cell line NEC8. The expressions of gankyrin, retinoblastoma and retinoblastoma protein were analyzed in 93 testicular germ cell tumor samples and five normal human testis by immunohistochemistry. The retinoblastoma protein expression was determined using an antibody to retinoblastoma protein, Ser795. Results Gankyrin was expressed in NEC8 cells as well as a normal human testis and testicular tumors. Suppression of gankyrin by locked nucleic acid led to suppression of retinoblastoma protein and cell proliferation in NEC8 cells. Immunohistochemistry of normal testis showed that gankyrin is expressed dominantly in spermatocytes. In testicular germ cell tumors, high expressions of gankyrin and phosphorylated‐retinoblastoma protein were observed in seminoma and embryonal carcinoma, whereas the expressions of both proteins were weak in histological subtypes of non‐seminoma. Growing teratoma and testicular malignant transformation tissues expressed phosphorylated‐retinoblastoma protein strongly, but gankyrin faintly. Conclusion Gankyrin is dominantly expressed in normal spermatocytes and seminoma/embryonal carcinoma, and its expression correlates well with retinoblastoma protein expression except in the growing teratoma and testicular malignant transformation cases. These data provide new insights into the molecular mechanisms of normal spermatogenesis and pathogenesis of testicular germ cell tumors.